ChemInform Abstract: Diversity‐Oriented General Protocol for the Synthesis of Privileged Oxygen Scaffolds: Pyrones, Coumarins, Benzocoumarins and Naphthocoumarins. Issue 50 (10th December 2013) - Goel, Atul; Taneja, Gaurav; Raghuvanshi, Ashutosh; Kant, Ruchir; Maulik, Prakas R.
Abstract Title compounds such as (IV), (VIII), and (XIII) are prepared through carbanion‐induced ring transformation of lactones such as (I), (V), and (X) with various methylene carbonyl compounds such as (II) and (VI), followed by DDQ‐mediated unprecedented oxidative cleavage of the C—C double bond.